The Impact of Corporate Governance (CGPI) and Investment Efficiency on Firm Value - Geovivo Ahsanti Mukminawati; Ario Purdianto (PT Keberlanjutan Strategis Indonesia, 2026)
Corporate governance and investment effectiveness's effects on a company's worth are the focus of this study. To measure the effectiveness of investments, one looks at the ROA, whereas the Corporate Governance Perception Index (CGPI) depicts corporate governance. The PBV ratio is a useful tool for assessing a company's worth. Businesses that are part of the CGPI and listed on IDX from 2021 to 2024 make up the study population. A total of 34 observational data points were obtained from the sample, which was selected using a purposive sampling strategy. This experiment makes use of SPSS software to construct multiple linear regression. A favourable but statistically negligible influence of corporate governance on business value was found, according to the data. On the other hand, corporate value is significantly and positively impacted by investment efficiency. Corporate governance and investment efficacy have a substantial impact on the value of the firm when considered collectively. CGPI and ROA variables account for approximately 14.7% of the fluctuations in firm value, as indicated by the adjusted R-squared value of 0.147. The remaining variance is likely driven by external elements outside the scope of this model, including macroeconomic trends, market volatility, and industry competition. These results suggest that investors prioritize a firm profitability in their evaluations, and the market has not yet fully acknowledged the benefits of robust governance practices on firm value. Therefore, this research recommends that businesses enhance their governance practices and optimize asset management efficiency to foster sustainable firm value.